White dwarf stars taking into account nuclear composition in general relativity - Boshkayev, K.A.; Zhami, B.A.; Kalymova, Zh.A.; Brisheva, Zh.N.; Taukenova, A.S.; Aimuratov, Y.K. (Recent Contributions to Physics, 2018)
In this work static cold white dwarfs are investigated by means of the Salpeter equation of state within general theory of relativity. The main parameters of white dwarfs such as mass, radius, central density and pressure are calculated solving the Tolman-Oppenheimer-Volkoff equation, employing the Salpeter equation of state. In addition, the white dwarf characteristics from the Sloan Digital Sky Survey Data Releases 4, 10 and 12 are analyzed. The histogram and the Gaussian distribution of mass and radius are constructed for the catalogues. The maximum, minimum and average values of the logarithm of the surface gravity, effective temperature, mass and radius are calculated. The theoretical mass-radius relations are compared with the observational data. Finally, it has been shown that taking into account nuclear composition, neutronization threshold, the Thomas-Fermi corrections and Coulomb interactions is very important to describe some white dwarfs in the catalogues of the Sloan Digital Sky Survey Data Releases 10 and 12.